ChemInform Abstract: Assignment of the Absolute Configurations of Natural Products by Means of Solid‐State Electronic Circular Dichroism and Quantum Mechanical Calculations. Issue 49 (3rd December 2013) - Pescitelli, Gennaro; Kurtan, Tibor; Krohn, Karsten
Abstract Review: 156 refs.